ANALYSIS OF THREATS TO GENERATORS OF PSEUDO-RANDOM NUMBERS AND PSEUDO-RANDOM SEQUENCES AND PROTECTION MEASURES - Khomik, Mariia; Harasymchuk, Oleh (Ukrainian Information Security Research Journal, 2023)
In the modern digital world with diverse applications, including cryptography, cybersecurity, and data protection, the issue of building reliable and secure pseudorandom number and sequence generators has become particularly significant. These generators create numerical sequences that appear random but are, in fact, deterministic and possess a certain structure, making them valuable in various fields. They are used for generating secret keys, ensuring confidentiality, data integrity, and transaction security, so their security is critical for applications that employ such generators. However, as the popularity and scope of pseudorandom number generators and pseudorandom sequence generators grow, so does their vulnerability to different types of attacks. Attacks on these generators can lead to the exposure of secret parameters and the compromise of security systems. Malicious actors and hackers seek various vulnerabilities in the methods and algorithms used to construct such generators to partially or fully disclose their operational principles. In this work, based on a thorough analysis of scientific publications by experts involved in the development, research, evaluation of quality, and application of pseudorandom number and sequence generators, the main vulnerabilities of these generators have been identified and described. Different types of attacks have been classified and described, and their impact on these generators has been determined. Security recommendations have been provided, and standards and testing methods have been identified to enhance the reliability, protection, and mitigation of vulnerabilities of such generators.